Waste Prevention and Social Preferences: The Role of Intrinsic and Extrinsic Motivations - Grazia Cecere; Susanna Mancinelli; Massimiliano Mazzanti (Fondazione Eni Enrico Mattei (FEEM), 2013)
Though reduction is at the top of the waste management hierarchy, EU policies have historically introduced waste management incentives mainly concerning waste recovery and recycling, in addition to actions aimed at reducing disposal in landfills. Only very recently have EU policies started defining targets for waste reduction. Against this backdrop, we aim to examine whether individual behavior towards waste reduction is more strongly driven by extrinsic motivations such as social norms, or intrinsic motivations such as purely altruistic preferences. We exploit a large new survey that covers thousands of individuals for the EU27, to test the role of motivations when people are faced with collective management of the public good. We find that diverse motivations are behind the reduction of food waste: extrinsic motivations nevertheless increase the likelihood of producing more waste. Green consumption / recycling-oriented attitudes and individualistic thinking about waste management relate to waste producers. This shows that in order to go beyond a recycling-oriented society towards reduction of the source of waste externality its generation the nature of social preferences matters. Behavior patterns leading to waste reduction are less socially oriented, less exposed to peer pressure and more reliant upon purely altruistic social attitudes. Policy makers should learn from the relevant insights on social behavior we here address if our societies aim to fully integrate the idea of waste reduction alongside recycling in the future.
Keywords: Q53; R11; K42; 330; Intrinsic Motivations; Extrinsic Motivations; Social Norms; Recycling; Waste Reduction; Green Preferences